Externally excited MILO - Gorban’, А.М.; Lonin, Yu.F. (Вопросы атомной науки и техники, 2013)
The numerical simulation method was applied to investigate the possibility of controlling the electromagnetic radiation from MILO-type devices using the external excitation by the signal with given characteristics. For this purpose a throttling section in the slow-wave structure of the oscillator is excited. The preliminary results obtained confirm the possibility of constructing a MILO-based externally excited oscillator capable to operate within the wide frequency range and in the broadband radiation mode.